Anti-Drug Antibodies in Pigtailed Macaques Receiving HIV Broadly Neutralising Antibody PGT121 - Lee, Wen Shi; Reynaldi, Arnold; Amarasena, Thakshila; Davenport, Miles P.; Parsons, Matthew S.; Kent, Stephen J. (Frontiers in Immunology, 2021)
Broadly neutralising antibodies (bNAbs) may play an important role in future strategies for HIV control. The development of anti-drug antibody (ADA) responses can reduce the efficacy of passively transferred bNAbs but the impact of ADA is imperfectly understood. We previously showed that therapeutic administration of the anti-HIV bNAb PGT121 (either WT or LALA version) controlled viraemia in pigtailed macaques with ongoing SHIV infection. We now report on 23 macaques that had multiple treatments with PGT121. We found that an increasing number of intravenous doses of PGT121 or human IgG1 isotype control antibodies (2-4 doses) results in anti-PGT121 ADA induction and low plasma concentrations of PGT121. ADA was associated with poor or absent suppression of SHIV viremia. Notably, ADA within macaque plasma recognised another human bNAb 10E8 but did not bind to the variable domains of PGT121, suggesting that ADA were primarily directed against the constant regions of the human antibodies. These findings have implications for the development of preclinical studies examining multiple infusions of human bNAbs.